Bruegel and beyond Netherlandish drawings in the Royal Library of Belgium, 1500-1800 - Heesch, Daan van 1992-; Ooteghem, Sarah van; Grieken, Joris van 1978- (Hannibal Books, 2022)
The Royal Library of Belgium in Brussels houses the largest collection of drawings in the country. Among its highlights are works by leading artists of the Low Countries, including Pieter Bruegel I, Joris Hoefnagel, Hendrick Goltzius, Peter Paul Rubens, Anthony van Dyck, and Jacques Jordaens. As the library's collection has been little studied up to now, it is largely unknown to scholars and the general public. To acquaint a wider audience with these important works of art, this richly illustrated publication brings together for the first time over one hundred master drawings from the Royal Library's vaults. Not only new art-historical insights are presented, but also numerous rediscovered drawings and revised attributions to artists such as Maarten van Heemskerck and Karel van Mander. This carefully researched book, written by thirty specialists in the field, aims to make a significant contribution to our knowledge of the history of Netherlandish drawing from the sixteenth to the eighteenth centuries
Keywords: Bibliothèque royale de Belgique; Geschichte 1500-1800; Sammlung; Zeichnung; Niederlande; Katalog; Bildband